ANALISIS PERAN PUBLIC SOCIAL SPENDING DALAM MENGENTAS KEMISKINAN - Sari, Maya Setia (Journal of Development Economic and Social Studies, 2023)
This study examines the condition of the poverty level in East Java. Despite of having high public social spending for poverty alleviation, East Java's poverty rate is still relatively high compared to the national average. This study aims to analyze the effectiveness of the role of public social spending in alleviating poverty in 38 districts/cities in East Java. The research analysis technique uses the 3SLS simultaneous equation model with panel data. The results of this study indicate that public social spending is proven to have a role in alleviating poverty in East Java in two ways. The first is that public social spending can alleviate poverty in East Java by providing cash subsidies to the poor as a social safety net. Second, public social spending in the form of education subsidies, health subsidies and employment subsidies can alleviate poverty in East Java through improving the quality of human resources which is responded by an increase in per capita income.